Expression and prognostic significance of vascular endothelial growth factor-A (VEGF-A) and its receptor in canine prostate cancer - Leis-Filho, Antonio Fernando [UNESP] (2021)
Background: Vascular endothelial growth factor-A (VEGF-A) and its receptor, VEGF receptor-2 (VEGFR-2), represent a complex family of angiogenic molecules consisting of different ligands and receptors. Due to the importance of VEGF-A/VEGFR-2 signaling in tumor proliferation and angiogenesis, this study aimed to evaluate the protein and gene expression levels of VEGF-A and VEGFR-2 in canine prostate cancer (PC). Methods: We analyzed VEGF-A and VEGFR-2 expression in 87 PC samples by immunohistochemistry and quantitative-polymerase chain reaction. PC samples were graded according to the Gleason score and the immunohistochemical staining for VEGF-A and VEGFR-2 was quantified using a selected threshold from the ImageJ Software. Microvascular density was assessed by cluster of differentiation 31 staining and counting the number of positive vessels. Additionally, the homology of VEGF-A and VEGFR-2 between humans and dogs was assessed, followed by the construction of a protein structure homology model to compare the tertiary structures of these proteins in both species. Results: Negative to weakly positive expression levels of VEGF-A and VEGFR-2 were observed in the epithelial cells of the normal prostate (NP) and prostatic hyperplasia samples. In contrast, the canine proliferative atrophy and PC samples exhibited higher VEGF-A (p <.0001) and VEGFR-2 (p <.0001) compared to NP. Moreover, positive correlations between the expression levels of VEGF-A and VEGFR-2 (Spearman's coefficient (r) =.68, p =.013) and the expression levels of VEGF-A and VEGFR-2 proteins (r =.8, p <.0001) were also observed in the NP samples. Additionally, the patients with PC exhibiting higher VEGFR-2 expression levels experienced a shorter survival period (p =.0372). Furthermore, we found an association between the microvascular density and overall survival. Dogs with a higher number of vessels showed a shorter survival time. We further demonstrated that the VEGF-A and VEGFR-2 exhibited high homology between humans and dogs, and identified their protein structures in both species. Conclusions: In conclusion, VEGFR-2 appears to be an independent prognostic factor in animals with PC. VEGF-A and VEGFR-2 are highly conserved between humans and dogs, which can be investigated further in future cross-species studies to explore their therapeutic applications.